Analysis of towing-gear concepts using iceberg towing simulations - Vetter, Christin; Ulrich, Christian; Rung, Thomas (ASME, 2011)
The paper reports on the development and application of an iceberg towing simulation procedure, whose efficiency allows an on-board use. Different solution techniques for the integration of the governing equations are compared with respect to performance and accuracy. Supplementary, the predictive accuracy of the employed rope models is outlined. Moreover, the merits of two different concepts for the towing gear set-up, i.e. utilizing a floating polypropylene part together with a submerged steel hawser or a single floating line, are discussed. Investigated application examples focus on towing medium sized icebergs with changes in ship speed. Based on a given towing speed profile, the acting forces and accelerations on the iceberg and the rope tension are simulated. Furthermore, the influence of modelling parameters, e.g. added hydrodynamic masses, is reported.